2010
DOI: 10.1203/pdr.0b013e3181eb5d68
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Protein-C Promoter Variants Associated With Neonatal Respiratory Distress Syndrome Reduce Transcription

Abstract: Dominant mutations in coding regions of the surfactant protein-C gene, SFTPC, cause respiratory distress syndrome (RDS) in infants. However, the contribution of variants in noncoding regions of SFTPC to pulmonary phenotypes is unknown. By using a case-control group of infants Ն34 weeks gestation (n ϭ 538), we used complete resequencing of SFTPC and its promoter, genotyping, and logistic regression to identify 80 single nucleotide polymorphisms (SNPs). Three promoter SNPs were statistically associated with neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…A smaller group of individuals have reduced SP-C levels and decreased mRNA expression without the generation of aberrant forms of the proprotein. Specifically, a single study identified three infants with respiratory distress syndrome associated with mutations in the SFTPC promoter that decreased expression without introducing any distortion of SP-C biosynthesis (7). Together, these reports suggest a compound disease pathogenesis from both the absence of mature SP-C and/or from cellular stress induced by malformed proSP-C.…”
Section: Discussionmentioning
confidence: 93%
“…A smaller group of individuals have reduced SP-C levels and decreased mRNA expression without the generation of aberrant forms of the proprotein. Specifically, a single study identified three infants with respiratory distress syndrome associated with mutations in the SFTPC promoter that decreased expression without introducing any distortion of SP-C biosynthesis (7). Together, these reports suggest a compound disease pathogenesis from both the absence of mature SP-C and/or from cellular stress induced by malformed proSP-C.…”
Section: Discussionmentioning
confidence: 93%
“…DNA was isolated from blood (n = 180), frozen lung tissue (n = 4), and saliva (n = 1) using commercially available kits as previously described (15,20). Sequence analysis of the coding exons and flanking introns was performed for all subjects as previously described (15,20).…”
Section: Mutational Analysismentioning
confidence: 99%
“…Sequence analysis of the coding exons and flanking introns was performed for all subjects as previously described (15,20).…”
Section: Mutational Analysismentioning
confidence: 99%
“…SP-C related disease can occur as acute postnatal respiratory distress or with slow onset that is identified as respiratory insufficiency during childhood through adulthood [2,3]. The molecular pathogenesis of SP-C related lung disease includes loss of gene expression without defined mutations, decreased expression from non-coding promoter mutations, and most commonly mutations in the SP-C coding gene ( SFTPC ) [4-6]. The SFTPC mutations have distinct consequences, altering mRNA splicing, proprotein structure, protein expression, or processing.…”
Section: Introductionmentioning
confidence: 99%